Basic Sciences Self-Test (Out of Print) - Raziel Hakim (Association of American Medical Colleges, 2007)
Abstract This web-based self-assessment program is a collection of over 3,000 multiple-choice, true-false, matching, and extended matching questions. Users can create customized quizzes by selecting the number and difficulty level of questions from a variety of topics within the fields of cell biology, histology, gross anatomy, and neuroanatomy. After completing a quiz, a score and list of questions taken are presented. Questions answered incorrectly are highlighted, and selecting any question returns the user to that question; the correct answer is highlighted, and explanations or references may be present. In the author's experience, the implementation was most effective when (1) it was used for credit as it incentivized completion, (2) required quizzes were completed after studying, (3) a predetermined pass level (i.e., 80% for medical students) was set, and (4) students were permitted to repeat quizzes until they passed. When the quizzes are used as part of a course, the pass rates of the students appear to increase. We recommend that a user register the first time they access the site and then log in. Registered students can review their previous quizzes. Faculty with administrative access can create new questions, sort copies of questions already present into new topics, view aggregate data on usage, and review data on use of any individual question. For more information, contact the author.